A framework to identify factors influencing navigational risk for Maritime Autonomous Surface Ships. (15th April 2020) - Fan, Cunlong; Wróbel, Krzysztof; Montewka, Jakub; Gil, Mateusz; Wan, Chengpeng; Zhang, Di
Abstract: Maritime Autonomous Surface Ships (MASS) have recently drawn significant attention throughout academia, governments, and industry. One of the requirements for MASS is that they should at least be as safe as conventional ships. Often, to measure their level of safety, the concept of risk is adopted, and risk influencing factors are determined. This paper proposes a framework for the identification of factors that influence the navigational risk of remotely controlled MASS without crews on board. Therein, four operational phases are considered: voyage planning, berthing and unberthing, port approaching and departing, as well as open sea navigation. For each phase, four types of factors are assigned related to human, ship, environment, and technology. To populate the framework, a thorough literature review is conducted, which is further supported by the elicitation of expert knowledge. As a result, 23 human-related factors, 12 ship-related factors, 8 environment-related factors, and 12 technology-related factors were defined. The proposed framework can be employed for any risk and safety analysis related to remote-controlled MASS. This, in turn, may assist the processes of design and operational planning of maritime transportation systems accommodating MASS and its remote-control center, e.g., the shore control center. Highlights: Risk influencing factors (RIF) for Maritime Autonomous Surface Ship operating at third degree of autonomy (MASS DoA3) is investigated. A 4P4F framework is proposed to identify RIF on MASS DoA3, focusing on 4 operational phases and 4 types of factors. Literature and experts' experience are utilized for identifying RIF and assigning them into 4 operational phases. 23 human factors, 12 ship factors, 8 environment factors, and 12 technology factors are identified as RIFs related to MASS DoA3 navigation.